Harness horses, bucking broncos & pit ponies : a history of horse breeds - Crosby, Jeff (Tundra Books, 2011)
The author-illustrator team of Jeff Crosby and Shelley Ann Jackson celebrates all kinds of horses in this beautifully illustrated, fact-filled book.